Some New Inequalities of Hermite-Hadamard Type for (α1, m1)-(α2, m2)-Convex Functions on Coordinates. (19th January 2014) - Chun, Ling
Abstract : The author introduces a new concept "(α 1, m 1 )-(α 2, m 2 )-convex functions on coordinates" and establishes some new inequalities of Hermite-Hadamard type for (α 1, m 1 )-(α 2, m 2 )-convex functions of two variables on co-ordinates.